Mapping of RORγt+ dendritic cells in human tissues establishes their preferential niche in adult lymph nodes - Lonardi, Silvia; Bianchetto-Aguilera, Francisco MA; Monti, Matilde; Di Matteo, Anna; Missale, Francesco; Picinoli, Sara; Bugatti, Mattia; Benedetti, Martina; Ferrari, Giorgia; Cassatella, Marco A.; Moratto, Daniele; Zini, Stefania; et al. (Frontiers in Immunology, 2025)
BackgroundThe retinoic-acid-receptor-related orphan receptor gamma t (RORγt) isoform is required for the development of lymphoid organs, T-helper 17 cells (Th17), and innate lymphoid cells (ILC3s). Recent data in mouse and human have revealed non-T, non-ILC3 cell populations with antigen presenting features that express RORγt. This study maps the presence of RORγt cells with dendritic cell (DC) features in human adult and fetal lymphoid tissues.MethodsBy combining multicolor flow cytometry, RNAseq of peripheral blood cells, analysis of lymph node scRNAseq datasets, and microscopic analysis on human tissue sections and single-cell suspensions, this study maps the presence of RORγt cells with DC features in human tissues.ResultsRORγt-DCs are found in human lymphoid organs, particularly in lymph nodes. Lymph node RORγt-DCs are located in the interfollicular area surrounding high endothelial venules and in the marginal sinuses. In terms of phenotype, RORγt-DCs are distinct from other nodal dendritic cells. They express PRDM16 and PIGR as well as transcripts supporting the antigen presentation machinery, while lacking stromal markers. A significant fraction of RORγt-DCs is proliferating, suggesting local self-renewal. Moreover, most of them lack autoimmune regulator (AIRE) expression. Comparison with mouse RORγt Thetis cells (TC) and Janus cells (JC) shows more similarity with group II TC than group I and III TC or JC, all of which are tolerogenic and express AIRE.ConclusionOverall, this study identifies human lymph nodes as a relevant niche for RORγt-DCs and establishes tools for their microscopic mapping in human disease states.